Vitamin C content of citrus from conventional versus organic farming systems - Duarte, Amílcar (2012)
Fertilization in citrus is a cultural practice with great importance as it affects significantly the quality of fruit. In this work we evaluated the effects of organic versus conventional farming systems on internal and external characteristics of citrus, with particular emphasis on vitamin C content. The study was carried out in different orchards of the Algarve region, in the south of Portugal. Fruits of different orchards were harvested at physiological maturity and submitted to physical and chemical analyses. The results showed that mineral fertilization led to fruits with greater weight and diameter, a thicker peel and a more intense colour. Compared with conventional production, fruits from organic farming had more soluble solids and a lower maturation index. The highest concentrations of vitamin C were recorded in fruits from organic farming, but the response depended on species and cultivar.